A new benchmark reference solution for double-diffusive convection in a heterogeneous porous medium. (1st November 2016) - Shao, Qian; Fahs, Marwan; Younes, Anis; Makradi, Ahmed; Mara, Thierry
ABSTRACT: A new benchmark with a high accurate solution is proposed for the verification of numerical codes dealing with double-diffusive convection in a heterogeneous porous medium. The new benchmark is inspired by the popular problem of square porous cavity by assuming a stratified porous medium. A high accurate steady state solution is developed using the Fourier–Galerkin method. To this aim, the unknowns are expanded in double infinite Fourier series. The accuracy of the developed solution is assessed in terms of the truncation orders of the Fourier series. Comparison against finite element solutions highlights the worthiness of the proposed benchmark for numerical code validation.